Reflections about the health of teachers in the context of commodification of higher education - Santos, Daniel Alberto Santos e (2016)
The sociopolitical and economic changes intensified from the 90s produced several changes in the teaching work. Its organization model has required higher productivity and even more specialized professional qualification (work intensification), thus stimulating the emerging of new attributions. Such assignments have negatively reflected on these professionals’ health. Within this framework, the faculty began to live in environments based on the business logic, with bad working conditions, leading them to situations of overworking, stress and competition, besides weakening the interpersonal relations and crippling the adequate use of free time. Such aspects spoil the faculty’s life quality. In this context, and understanding that the way working conditions are set has a crucial role in the occupational health-disease process, the present paper aims to highlight the commodification process in the Brazilian universities and its effects on teachers’ health.